Educación Musical para la Paz: Proyectos musicales con fines sociales (2021)
Musical programs with a social vocation, currently widely spread throughout the world, constitute genuine professional spaces where music teachers play the role of peace mediators. There, music becomes a peace-building tool not only thanks to its expressive and artistic dimension, but also to the proper management of the pedagogical situations in which one learns. This article is a reflective essay based on an exploratory research on the music-social programs of the Batuta Foundation in Colombia and Démos in France. In these cases, music education for peace can be considered as a process of cultural democratization, in which creativity, group dynamics and territorial social inclusion are developed, and where planning and pedagogical innovation are essential. Teacher training must therefore adapt to these new challenges and needs of contemporary society.